Role of Plasminogen Activator Inhibitor Type 1 in Pathologies of Female Reproductive Diseases - Ye, Yao (Int J Mol Sci, 2017)
Normal pregnancy is a state of hypercoagulability with diminishing fibrinolytic activity, which is mainly caused by an increase of plasminogen activator inhibitor type 1 (PAI-1). PAI-1 is the main inhibitor of plasminogen activators, including tissue-type plasminogen activator (tPA) and urokinase-type plasminogen activator (uPA). In human placentas, PAI-1 is expressed in extravillous interstitial trophoblasts and vascular trophoblasts. During implantation and placentation, PAI-1 is responsible for inhibiting extra cellular matrix (ECM) degradation, thereby causing an inhibition of trophoblasts invasion. In the present study, we have reviewed the literature of various reproductive diseases where PAI-1 plays a role. PAI-1 levels are increased in patients with recurrent pregnancy losses (RPL), preeclampsia, intrauterine growth restriction (IUGR), gestational diabetes mellitus (GDM) in the previous pregnancy, endometriosis and polycystic ovary syndrome (PCOS). In general, an increased expression of PAI-1 in the blood is associated with an increased risk for infertility and a worse pregnancy outcome. GDM and PCOS are related to the genetic role of the 4G/5G polymorphism of PAI-1. This review provides an overview of the current knowledge of the role of PAI-1 in reproductive diseases. PAI-1 represents a promising monitoring biomarker for reproductive diseases and may be a treatment target in the near future.